Pesticides detected in surface and groundwater from agroecosystems in the Pampas region of Argentina: occurrence and ecological risk assessment - Vera Candioti, Josefina; Araujo, Patricia Ines; Huerga, Ignacio Roberto; Rojas, Dante Emanuel; Cristos, Diego Sebastian; Malmantile, Alberto (Springer, 2021)
The objective of this study was to evaluate the occurrence of pesticides in surface and groundwater of agricultural areas of the Pampas region of Argentina and to develop an ecological risk assessment (ERA) of pesticides in freshwater ecosystems. Eight agricultural sites from south Santa Fe province, in the north of the Pampas region, were sampled seven times between 2016 and 2018. Pesticides were analysed by gas chromatography-mass spectrometry (GC/MS) and liquid chromatography-mass spectrometry (UPLC-LC/MS). Twenty compounds among herbicides, insecticides and fungicides in 84% and 79% of groundwater and surface water samples, respectively, were detected. Atrazine was the most ubiquitous pesticide, following by metolachlor, acetochlor and glyphosate, with maximum concentrations of 28, 24, 77 and 111 µg/L, respectively. An ERA was performed by employing the risk quotient (RQ) method. Atrazine, azoxystrobin, pirimiphos-methyl, acetochlor and epoxiconazole posed a high and very high risk for aquatic organisms (RQ > 1) and glyphosate, metolachlor and 2,4-D exhibited negligible to medium risk. The herbicides were the major contributors to risk. This study is the first contribution on the presence and concentration of pesticides in surface and groundwater from agricultural areas of south Santa Fe province, north Pampas region, Argentina, and a starting point for pesticide ecological risk assessment.